Peran Guru Dalam Pembimbingan Belajar Al-Qur’an di SMP Muhammadiyah 1 Gatak - Istaluhu, Rahman; Dartim, Dartim (LP. Ma'arif Janggan Magetan, 2023)
There are so many students whose ability to read the Qur'an is still lacking, some are even unable to read at all, therefore this form of guidance on how to read the Qur'an is a form of learning so that students are able to read the Qur'an. This will also help Islamic teachers in providing Islamic religious learning in schools. This research is a type of qualitative descriptive research with several activities that include data collection techniques, namely by conducting observations, interviews and documentation. Data analysis techniques use descriptive techniques or more specifically use interactive models. The results of this research are: (1) The teacher's role in guiding learning to read the Al-Qur'an must really be implemented as well as possible. The teacher's role includes increasing study hours and guiding students in extracurricular reading of the Koran. (2) Steps taken include providing additional Al-Qur'an study hours, to maximize student learning activities. Then provide guidance in the extracurricular Al-Qur'an reading program, with the aim of all students being able to read the Al-Qur'an well. This is done considering that relying on the available hours is very small to achieve success in students being able to read the Al-Qur'an well and correctly.